The cost-effectiveness of iruplinalkib versus alectinib in anaplastic lymphoma kinase-positive crizotinib-resistant advanced non-small-cell lung cancer patients in China - Zhanjing Dai; Jiayi Xu; Feng Chang; Wanxin Zhou; Ting Ren; Jiaxin Qiu; Yun Lu; Yuqiong Lu (Frontiers Media S.A., 2024)
BackgroundIruplinalkib is a second-generation anaplastic lymphoma kinase (ALK) tyrosine kinase inhibitor (TKI) with efficacy in patients with ALK-positive crizotinib-resistant advanced non-small cell lung cancer (NSCLC), which is independently developed by a Chinese pharmaceutical company. This study examined the cost-effectiveness of iruplinalkib versus alectinib in the Chinese healthcare setting.MethodsA partitioned survival model was developed to project the economic and health outcomes. Efficacy was derived using unanchored matching-adjusted indirect comparison (MAIC). Cost and utility values were obtained from the literature and experts' opinions. Deterministic and probabilistic sensitivity analyses (PSA) were carried out to evaluate the model's robustness.ResultsTreatment with iruplinalkib versus alectinib resulted in a gain of 0.843 quality-adjusted life years (QALYs) with incremental costs of $20,493.27, resulting in an incremental cost-effectiveness ratio (ICER) of $24,313.95/QALY. Parameters related to relative efficacy and drug costs were the main drivers of the model outcomes. From the PSA, iruplinalkib had a 90% probability of being cost-effective at a willingness-to-pay threshold of $37,863.56/QALY.ConclusionCompared to alectinib, iruplinalkib is a cost-effective therapy for patients with ALK-positive crizotinib-resistant advanced NSCLC.